A DETERMINANT MODEL OF TUBERCULOSIS TREATMENT COMPLIANCE MANAGEMENT BASED ON BEHAVIOR, FAMILY SUPPORT, AND HEALTH WORKERS: BATAM CASE STUDY - Elzusandry Fithri; Herdianti Herdianti; Sabri Sabri; Hendri Herman; Hengky Oktarizal (Universitas Negeri Gorontalo, 2026)
Adherence to Anti-Tuberculosis Drugs (ATD) is a primary determinant of successful TB therapy and prevention of drug resistance. Non-adherence significantly contributes to treatment failure, relapse, and increased public health burden, especially in high-mobility urban areas such as Batam City. The novelty of this study lies in the simultaneous integration of patient behavior, family support, and healthcare worker roles into a single determinant model of TB treatment adherence management in an archipelago urban context. This study aimed to analyze factors affecting ATD adherence among pulmonary TB patients at Baloi Permai Primary Health Center, Batam. A quantitative cross-sectional study with a statistical model output was conducted on 142 pulmonary TB patients undergoing treatment from July 2025 to April 2026 using total sampling. Data were collected through validated structured questionnaires and analyzed using chi-square tests and Backward Stepwise logistic regression. Bivariate analysis revealed that attitude (p=0.043) and family support (p=0.001) significantly influenced ATD adherence. Multivariate analysis identified family support as the dominant determinant with an Odds Ratio of 6.313 (95% CI=1.557–25.606; p=0.010), indicating that patients receiving good family support were 6.313 times more likely to adhere to treatment than those without adequate support. It is concluded that family support is the primary determinant of ATD adherence. Strengthening family involvement in TB management programs at primary health centers, through education, motivation, and optimization of family Drug Supervision roles, should be prioritized as an intervention strategy.